Split quaternion Fourier transforms for two-dimensional real invariant field - Kim Ji Eun (Demonstratio Mathematica)
The article gives the corresponding split quaternions in Clifford analysis and the split Fourier transform (FT). Also, we investigate some properties of the split FT and apply to generalizations of the quaternion FT.